INTEGRATION OF SMART TECHNOLOGIES INTO THE MODERN EDUCATIONAL PROCESS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the essence, features, and potential of smart technologies in the vocational education system. The study highlights the transition from traditional teaching methods to innovative smart technologies and analyzes their impact on the development of students’ professional competencies. Based on the analysis of scientific sources, the paper defines the main directions, goals, and tasks of implementing smart technologies in the educational process. The role of tools such as gamification, case-based learning, web quests, mobile and project-based learning in improving the quality and interactivity of education is discussed.